The Influence of Electronic Word of Mouth on Intentions to Purchase Ticket Hotel Booking Through Traveloka Platform - Fanesa Widya Oktavia Butar Butar; Heppy Millanyani (Green Publisher Indonesia, 2025)
The advancement of technology has transformed various industries, including tourism. Online Travel Agents (OTA) have revolutionized travel booking, offering convenience and accessibility. Platforms like Traveloka allow customers to compare prices, read reviews, and make informed decisions. Electronic Word of Mouth (eWOM) plays a crucial role in influencing consumer behavior, as positive online reviews significantly impact purchasing decisions and brand perception. This research aims to analyze the impact of electronic Word of Mouth (eWOM) on hotel ticket purchase intentions through the Traveloka platform, with a focus on the mediating role of eWOM adoption. Specific objectives include examining the significance of eWOM dimensions, consumer trust, and review credibility in influencing purchase decisions. This research employs the Structural Equation Modeling-Partial Least Squares (SEM-PLS) methodology to analyze relationships between eWOM dimensions and hotel ticket purchase intentions. SEM-PLS is chosen for its ability to handle complex models and evaluate latent constructs. The findings are expected to provide insights into the significance of eWOM in shaping consumer behavior and offer strategic implications for Traveloka and similar OTAs in optimizing marketing strategies.